3D cinema and beyond - Adler, Dan; Marchessault, Janine; Obradovic, Sanja (Public Books, 2013)
The editors brings together essays that engage with mainstream entertainment, experimental film, and historical scholarship as part of a larger context for examining the grammar of 3D cinema, its histories, and its futures. From cinema and television to video games and augmented reality, the essays consider an 'expanded field' of stereoscopic visual culture.